2015
DOI: 10.1111/are.12828
|View full text |Cite
|
Sign up to set email alerts
|

The effect of exogenous enzyme supplementation on growth performance and digestive enzyme activities inOreochromis mossambicusfed kikuyu-based diets

Abstract: The utilization of plant‐based diets in fish is limited by the presence of anti‐nutrients, which bind to dietary nutrients and reduce their bioavailability. Exogenous enzyme supplementation may alleviate the effects of anti‐nutrients and improve feed utilization. In this study, a commercial multi‐enzyme Natuzyme50® was added to a kikuyu‐based diet at a rate of 0 (control), 0.25, 0.5, 0.75 and 1.00 g kg−1 DM. Each diet was fed to triplicate groups of Oreochromis mossambicus for 60 days. All fish fed diets conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 26 publications
5
27
0
Order By: Relevance
“…In the present study, the activity of lipase and trypsin in the liver and intestines of the fish in all the experimental groups was significantly increased compared to that in the control group, which was consistent with the results of Lin et al () who supplemented the multienzyme complex in diets, The activity of protease and amylase in the intestine and hepatopancreas of tilapia were observed improving significantly. Furthermore, the addition of 0.5 g/kg EC could significantly improve the digestive enzyme activities of tilapia in the experiment of Hlophe‐Ginindza et al (), and the activity of protease, amylase and lipase in hepatopancreas of Penaeus vannamei were also observed significantly improving by the addition of supplement 175 mg/kg protease in diets (Song et al, ).The improvement of the digestive enzyme activity was also probably due to the substrates and anti‐nutrition factors hydrolysed which makes the diet to digest easily (Ai et al, ). A significant decrease in the activity of amylase in the fish intestine was observed in the EC4 group.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In the present study, the activity of lipase and trypsin in the liver and intestines of the fish in all the experimental groups was significantly increased compared to that in the control group, which was consistent with the results of Lin et al () who supplemented the multienzyme complex in diets, The activity of protease and amylase in the intestine and hepatopancreas of tilapia were observed improving significantly. Furthermore, the addition of 0.5 g/kg EC could significantly improve the digestive enzyme activities of tilapia in the experiment of Hlophe‐Ginindza et al (), and the activity of protease, amylase and lipase in hepatopancreas of Penaeus vannamei were also observed significantly improving by the addition of supplement 175 mg/kg protease in diets (Song et al, ).The improvement of the digestive enzyme activity was also probably due to the substrates and anti‐nutrition factors hydrolysed which makes the diet to digest easily (Ai et al, ). A significant decrease in the activity of amylase in the fish intestine was observed in the EC4 group.…”
Section: Discussionmentioning
confidence: 93%
“…In the present study, the addition of 1.5 g/kg EC had the best effect on the final weight, the weight gain rate, the specific growth rate and the feed conversion of the Japanese seabass, which was consistent with the results of Lin, Mai, and Tan () who found that the specific growth rate and feed utilization of tilapia ( Oreochromis niloticus × O. aureus ) were significantly improved by the supplementation of 1.5 g/kg EC composed of neutral protease, β‐glucanese and xylanase. Meanwhile, increased growth performance was also observed in the results of Ghomi, Shahriari, Langroudi, Nikoo, and von Elert () and Hlophe‐Ginindza, Moyo, Ngambi, and Ncube () who found the significantly enhanced growth performance of great sturgeon fingerlings ( Huso huso ) and tilapia ( Oreochromis mossambicus ) by the supplementation of multienzyme complex composed of protease and xylanase. The effect of EC on the growth performance of fish may be related to the increase of nutrient absorption and digestive capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ghomi et al () reported that great sturgeon ( Huso huso ) fingerlings fed with 250 mg/kg exogenous multienzyme complex contains phytase, lipase, xylanase, protease, β‐glucanase, ɑ‐amylase, pentosanase, hemicellulase, cellulase and pectinase, exhibited higher weight gain and specific growth rate, and also significantly improved feed conversion ratio. Similarly, it was also reported that fed diets containing multienzyme Natuzyme50 ® (Bioproton) containing protease, phytase, xylanase, β‐glucanase, ɑ‐amylase and cellulase could significantly increase protein digestibility and digestive enzyme activities of tilapia, and promote its growth performance (Hlophe‐Ginindza et al, ). Diógenes et al () demonstrated that turbot ( Scophthalmus maximus ) juveniles fed diets with Natugrain ® TS, BASF (NAT) containing endo‐1,4‐beta‐xylanase (5,600 TXU/g) and endo‐1,4‐beta‐glucanase (2,500 TGU/g) significantly increased the apparent digestibility coefficient and digestive enzyme activity in the posterior intestine of fish.…”
Section: Perspectives and Opportunities For Exogenous Enzyme Supplemementioning
confidence: 99%
“…While fish lack the enzyme to hydrolyse phytate phosphorus in the digestive system, therefore, the phosphorus combined with phytic acid cannot be absorbed and utilized by fish in the feed, resulting in a pollution of phosphorus discharged into water. The use of exogenous phytase can transform the phytic acid‐bound phosphorus into the available phosphorus of fish, thus improving the utilization rate of phosphorus in feed and reducing pollution To enhance growth performance and optimize whole‐body composition (Deguara, ; Ghomi et al, ; Hlophe‐Ginindza et al, ; Hung et al, ; Kolkovski et al, ; KuzMina & Golovanova, ; Li et al, ; Liu et al, ; Xavier et al, ). It was observed that the growth performance of larvae was lower when feeding formula feed, which may be due to their incomplete development of digestive tract with insufficient enzyme activity for the formulated diets (Kolkovski et al, ).…”
Section: Introductionmentioning
confidence: 99%